Risk Management & Priority Setting - Damani, Nizam (International Journal of Infection Control, 2009)
Key points • It is the responsibility of the Infection Control Team to identify infection control practices which are unsafe and hazardous. • Unsafe practices must be assessed for their likely severity and frequency. • Priority must be given to hazardous practices that have high adverse effects, occur more frequently and have low cost to prevent. • Effectiveness of these measures should be monitored by regular audit and/or surveillance and the information must be fed back to front-line clinical staff and relevant managers.